leafy hull sterile1 Is a Homeotic Mutation in a Rice MADS Box Gene Affecting Rice Flower Development - Jeon, Jong-Seong (American Society of Plant Physiologists, 2000)
Rice contains several MADS box genes. It has been demonstrated previously that one of these genes, OsMADS1 (for Oryza sativa MADS box gene1), is expressed preferentially in flowers and causes early flowering when ectopically expressed in tobacco plants. In this study, we demonstrated that ectopic expression of OsMADS1 in rice also results in early flowering. To further investigate the role of OsMADS1 during rice flower development, we generated transgenic rice plants expressing altered OsMADS1 genes that contain missense mutations in the MADS domain. There was no visible alteration in the transgenic plants during the vegetative stage. However, transgenic panicles typically exhibited phenotypic alterations, including spikelets consisting of elongated leafy paleae and lemmas that exhibit a feature of open hull, two pairs of leafy palea-like and lemma-like lodicules, a decrease in stamen number, and an increase in the number of carpels. In addition, some spikelets generated an additional floret from the same rachilla. These characteristics are very similar to those of leafy hull sterile1 (lhs1). The map position of OsMADS1 is closely linked to that of lhs1 on chromosome 3. Examination of lhs1 revealed that it contains two missense mutations in the OsMADS1 MADS domain. A genetic complementation experiment showed that the 11.9-kb genomic DNA fragment containing the wild-type OsMADS1 gene rescued the mutant phenotypes. In addition, ectopic expression of the OsMADS1 gene isolated from the lhs1 line resulted in lhs1-conferred phenotypes. These lines of evidence demonstrate that OsMADS1 is the lhs1 gene.